2006
DOI: 10.1007/s11524-006-9051-8
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Capital and Self-Rated Health in Low Income Women: Evidence from the Urban Health Study, Beirut, Lebanon

Abstract: This paper examines the association between cultural capital and self-rated psychosocial health among poor, ever-married Lebanese women living in an urban context. Both self-rated general and mental health status were assessed using data from a cross-sectional survey of 1,869 women conducted in 2003. Associations between self-rated general and mental health status and cultural capital were obtained using chi (2) tests and odds ratios from binary logistic regression models. Cultural capital had significant asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 53 publications
(93 reference statements)
2
42
1
Order By: Relevance
“…The difference in the training of healthcare providers is noted throughout the interviews, as interviewees who used private healthcare typically used physician-specific terms such as 'gynaecologist' or 'General Practitioner', while the women accessing public care typically referred to providers as 'nurse', 'sister' or 'tester'. Most studies on healthcare and cultural capital have focused on the cultural capital of patients (Khawaja and Mowafi 2006;Shim 2010). However, in settings such as South Africa, where there is significant disparity between healthcare facilities (McIntyre et al 2008) and patients have such varying experiences, the cultural capital of healthcare providers is also important to consider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the training of healthcare providers is noted throughout the interviews, as interviewees who used private healthcare typically used physician-specific terms such as 'gynaecologist' or 'General Practitioner', while the women accessing public care typically referred to providers as 'nurse', 'sister' or 'tester'. Most studies on healthcare and cultural capital have focused on the cultural capital of patients (Khawaja and Mowafi 2006;Shim 2010). However, in settings such as South Africa, where there is significant disparity between healthcare facilities (McIntyre et al 2008) and patients have such varying experiences, the cultural capital of healthcare providers is also important to consider.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence exists that cultural capital is associated with health status, even within populations of similar socioeconomic standing. For instance, a study in Lebanon found that women with low cultural capital were significantly more likely to report poor general and mental health compared to those with high cultural capital, even when participants were of the same socioeconomic status (Khawaja and Mowafi 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Social capital in urban areas plays an important role in determining individual health risks and outcomes (49,56). Network social capital refers to resources accessed through one's social connections and can be measured using a position generator instrument.…”
Section: Social Environmentmentioning
confidence: 99%
“…Following Abel (2008), cultural activities such as arts attendance may also reflect socioeconomic status, and it is well-known that individuals with higher incomes or better education tend to be healthier than others (for a review, see Cutler et al, 2011). Similarly, Khawaja and Mowafi (2006) argue that cultural activities could reflect social stratification in society. To maintain and accumulate their social status, individuals invest accordingly in cultural capital, for example via visits to arts events.…”
Section: Previous Literaturementioning
confidence: 99%
“…Cultural activities can thus be seen as a form of social capital that can be used as inputs in health production (e.g. Folland, 2008) Several empirical studies using individual-level survey data have found a positive association of cultural-event attendance with perceived health in various populations (Cuypers et al, 2012;Johansson et al, 2001;Khawaja and Mowafi, 2006;Renton et al, 2012;Wilkinson et al, 2007). It is questionable, however, whether the observed correlations reflect causal effects of arts participation on health.…”
Section: Previous Literaturementioning
confidence: 99%